Web-Based Psychotherapy and Exercise Interventions for Depressive and Anxiety Disorders - Carneiro, Lara (2021)
The last decade has seen a renewed recognition of the interconnection of the mental and physical well-being of people living with anxiety and depression disorders. Research has assessed the impact of exercise and psychological interventions as monotherapy and complementary treatments to usual care and found considerable benefits to reduce psychiatric symptoms and improve better quality of life. There is growing interest in online interventions, and online counseling can be an alternative to traditional face-to-face therapies. Questions remain on the effectiveness and best practices to deliver such interventions. The authors identify and summarize research evaluating online psychotherapy and exercise interventions in individuals with anxiety and depression disorders. They address web-based psychotherapy interventions and web-based exercise interventions for anxiety and depression disorders, followed by combined web-based intervention with psychotherapy and exercise, and discuss strategies to improve adherence to treatments.